The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpubh.2020.00325
|View full text |Cite
|
Sign up to set email alerts
|

Survival-Convolution Models for Predicting COVID-19 Cases and Assessing Effects of Mitigation Strategies

Abstract: Countries around the globe have implemented unprecedented measures to mitigate the coronavirus disease 2019 (COVID-19) pandemic. We aim to predict the COVID-19 disease course and compare the effectiveness of mitigation measures across countries to inform policy decision making using a robust and parsimonious survival-convolution model. We account for transmission during a pre-symptomatic incubation period and use a time-varying effective reproduction number ( R t ) to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…On the other hand, epidemiologic studies reported in this journal have progressed our understanding of the risk factors associated with SARS-CoV-2 transmission and COVID-19 fatal outcomes (13)(14)(15)(16)(17)(18)(19). Likewise, modeling studies have shed light on effective control measures and likely trajectory of the pandemic in various settings (20)(21)(22)(23).…”
Section: Use and Misuse Of Epidemiologic Surveillance Datamentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, epidemiologic studies reported in this journal have progressed our understanding of the risk factors associated with SARS-CoV-2 transmission and COVID-19 fatal outcomes (13)(14)(15)(16)(17)(18)(19). Likewise, modeling studies have shed light on effective control measures and likely trajectory of the pandemic in various settings (20)(21)(22)(23).…”
Section: Use and Misuse Of Epidemiologic Surveillance Datamentioning
confidence: 96%
“…They estimated that the lockdown effectively reduced the transmission of the COVID-19 by a factor 7, based on an effective reproduction number R e = 0.47 during lockdown compared to the basic reproduction number R 0 = 3.2 in the early stage of the epidemic (22). With yet another approach, Wang et al developed a survival convolution model to fit the dynamics of national epidemics and estimated the effect of nationwide control interventions in selected countries through a natural quasi-experimental design (23). Their forecasting results predicted better COVID-19 transmission control in China and Korea than in Italy and the USA after relaxing restriction measures in the spring 2020 (23).…”
Section: Use and Misuse Of Epidemiologic Surveillance Datamentioning
confidence: 99%
“…29,30 To this point, several restrictions levied have proven effective in slowing down the spread of COVID-19, but the greatest effect is obtained by applying a combination of measures. 27,31 Interestingly, during the 1918-19 Spanish Flu pandemic similar travel restrictions and quarantine measures were implemented in many countries. It is estimated that implementation of these measures during the 1918-19 pandemic resulted in a reduction of death rates by 50%.…”
Section: Mitigation Measuresmentioning
confidence: 99%
“…In early stages of the pandemic there was quite some confusion, particularly in western countries, about the protective effects of facial masks and physical distancing until the established evidence surfaced 29,30 . To this point, several restrictions levied have proven effective in slowing down the spread of COVID‐19, but the greatest effect is obtained by applying a combination of measures 27,31 . Interestingly, during the 1918‐19 Spanish Flu pandemic similar travel restrictions and quarantine measures were implemented in many countries.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The first group addressed the problem of forecasting the disease in order to help decision makers to better evaluate the logistic challenges they will face [1, 3, 4, 16, 15, 24, 25, 28, 29, 37, 38, 39, 41, 45, 47, 48, 51, 61, 62]. The second category of papers focused on evaluating the effectiveness of mitigations measures prescribed by the WHO and different governments in order to define better fighting strategies [5, 9, 12, 13, 14, 29, 34, 37, 41, 44, 45, 46, 50, 53, 55, 54, 60, 62]. The last set of papers studied the social and the economical impacts of the pandemic [35, 59].…”
Section: Introductionmentioning
confidence: 99%